English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

Prove the theorem using the basic axioms of algebra.

If ac = bc and c=/=0, then a = b.



It's my first time learning proofs. I just need this one example exlpained to me and I'll get it.

2007-05-21 07:00:59 · 6 answers · asked by booflouise 2 in Science & Mathematics Mathematics

6 answers

Here's a pseudo-proof below.

Assume ac = bc, and c is not equal to 0.
This means there exists a multiplicative inverse 1/c.

Multiply both sides by (1/c) from the RIGHT.

(ac)(1/c) = (bc)(1/c)

By associativity, this becomes

a(c * 1/c) = b(c * 1/c)

One of the axioms is that a number multiplied by its multiplicative inverse is 1.

a(1) = b(1)

By identity, a(1) = a, and b(1) = b, so

a = b

2007-05-21 07:06:37 · answer #1 · answered by Puggy 7 · 2 0

Given ac = bc and c not = 0
Prove a = b

ac= bc [Reason = Given]
c not = 0 [Reason = Given]
ac/c = bc/c [ Reason = Division axiom]
c/c = 1 [ Aquantity divided by itself = 1]
a*1 = b*1 [Substitution Axiom]
therefore a = b [muliplicative identity axiom]

2007-05-21 14:25:04 · answer #2 · answered by ironduke8159 7 · 0 0

ac=bc subtracting bc from both sides
ac - bc = 0 factor oout the common c
c(a-b) = 0 Now, for teh product to be 0, one of the factors must be 0 and, since c cannot be 0 (from the statement of the problem) we are left with
a-b = 0 and, adding b to both sides
a = b

BTW, proofs are the absolute --heart-- of all of mathematics. Learn them well and things will be much easier ☺

HTH

Doug

2007-05-21 14:17:17 · answer #3 · answered by doug_donaghue 7 · 1 0

ac = bc

ac/c = bc/c { Divided both sides by "c" }

a = b

The reason c can't be zero (0) is because you can't divide by zero.

2007-05-21 14:08:55 · answer #4 · answered by Dave 6 · 0 0

always hated proofs

2007-05-21 14:05:09 · answer #5 · answered by crzycutie6 3 · 0 0

no....not really.

2007-05-21 14:04:29 · answer #6 · answered by ? 1 · 0 0

fedest.com, questions and answers